THE EFFECT OF ENVIRONMENTAL ADAPTATION, HUMAN DEVELOPMENT INDEX AND INFLATION ON PROVINCIAL AND URBAN ECONOMIC GROWTH IN INDONESIA - Anggun Kinanti Tarigan; Cut Putri Mellita Sari (LPPM Universitas Malikussaleh, 2025)
This study aims to analyze how the Environmental Quality Index, Human Development Index, and Inflation affect Economic Growth at the provincial level in Indonesia. This study uses panel secondary data from 34 provinces in Indonesia for the period 2020 to 2024, obtained from official publications of the Central Statistics Agency (BPS) and the Ministry of Environment and Forestry (MoEF). To achieve the research objectives, a panel data regression analysis method was used with a Fixed Effect Model (FEM) approach processed using the Eviews-12 program. The results of the study show that partially, the variables of the Environmental Quality Index, Human Development Index, and Inflation have a positive and significant effect on economic growth, respectively. Simultaneously, these three variables also have a positive and significant effect on economic growth in Indonesia. These findings confirm that efforts to improve environmental quality, accelerate human development, and maintain inflation stability have an important role in encouraging sustainable economic growth at the regional level.